Carbon Absorption Potential in the Hungayono Karst Ecosystem, Tulabolo Pinogu Resort, Bogani Nani Wartabone National Park - Timbola, Muh Kirad; Katili, Abubakar Sidik; Husain, Ilyas H.; Kandowangko, Novri Youla; Mamu, Hartono D. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Climate change caused by increasing carbon dioxide (CO₂) emissions has become a global issue affecting environmental balance and rising global temperatures. Tropical forest ecosystems, including the Hungayono karst area in Bogani Nani Wartabone National Park, play an important role as carbon sinks through vegetation biomass. This study aims to analyze vegetation density, biomass, carbon content, and carbon sequestration potential in the Hungayono karst ecosystem. The research was conducted using a quantitative descriptive method with purposive sampling techniques at three observation points through the transect quadrat method. Vegetation data were analyzed using allometric equations and IPCC conversion factors. The results showed a tree density of 290 individuals/ha and sapling density of 335 individuals/ha. Total biomass reached 677.79 tons/ha, carbon content was 420.06 tons/ha, and carbon sequestration potential was 1541.63 tons CO₂e/ha. These findings indicate that tree-level vegetation plays a dominant role in carbon storage and climate change mitigation.